Enhancement of natural convection heat transfer in concentric annular space using inclined elliptical cylinder (Journal of Naval Architecture and Marine Engineering, 2020)
The governing equations of continuity, momentum and energy are numerically solved to study the laminar natural convection heat transfer of Newtonian fluid confined within two concentric cylinders. The inner cylinder is elliptical cross-section with different aspect ratio E = 0.1 to 0.5 and it is considered to be hot, whereas the outer cylinder is circular and it is supposed to be cold.    The annular spacing between the cylinders is defined based on radii ratio (RR = 2.5). Also, the inner cylinder is inclined with an inclination angle (θ = 0 to 90). The main purpose of this study is to determine the effects of inclination angle (θ = 0° to 90°), aspect ratio of inner cylinder (E = 0.1 to 0.5), Prandtl number (Pr = 0.71 and 7.01) and Rayleigh number (Ra = 103 to 105) on fluid flow and heat transfer rate. The flow patterns and temperature distributions are potted in terms of streamlines and isotherms respectively. The obtained results showed that increase in inclination angle enhances the heat transfer rate of inner cylinder for all values of aspect ratio. Also, for the inclination angle          (θ = 90°), the decrease in aspect ratio (E) improves the heat transfer rate of inner cylinder.